Quantum 2.0 Conference and Exhibition 2022
DOI: 10.1364/quantum.2022.qtu2a.4
|View full text |Cite
|
Sign up to set email alerts
|

Experimentally Realizable Continuous-variable Quantum Neural Networks

Abstract: We build a continuous variable hybrid quantum-classical neural network using only Gaussian gates. We achieve non-linearity through measurements on ancillary qumodes. Our protocol can be realized experimentally with current photonic technology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…It should be pointed out that the introduction of an ancilla qumode is similar to the training of CV Quantum Neural Networks (QNN) that are experimentally realizable, as we discussed in our previous work [16]. Here we aim at a similar construction that would yield experimentally realizable CVQBM.…”
Section: The Methodsmentioning
confidence: 96%
See 2 more Smart Citations
“…It should be pointed out that the introduction of an ancilla qumode is similar to the training of CV Quantum Neural Networks (QNN) that are experimentally realizable, as we discussed in our previous work [16]. Here we aim at a similar construction that would yield experimentally realizable CVQBM.…”
Section: The Methodsmentioning
confidence: 96%
“…Next, we apply our CVQBM to quantum data. We consider two cases: a Gaussian distribution and a non-Gaussian distribution (cat state) both of which are generated approximately by a quantum neural network (QNN) [16].…”
Section: Quantum Data Probability Distribution Generationmentioning
confidence: 99%
See 1 more Smart Citation
“…Another advantage of using continuous variable architectures is that they are easily implementable experimentally, for example using photonic quantum computers. A recent proposal with a focus on the experimental implementation is given for example in [27], while extensive reviews on this topic can also be found in [1,28].…”
Section: A Continuous Quantum Perceptron Modelmentioning
confidence: 99%
“…Firstly, in this appendix, we keep the input bias m in fixed and let mout → 1 − ; then, in the next one we treat the case when m in = mout = m → 1 − . Consider the equation with a±(M) as in (27). If mout → 1 − and m in is kept fixed, M must diverge to +∞.…”
Section: Appendix B Large Output Bias Limitmentioning
confidence: 99%